Clinical case report: considerable improvement of severe and difficult-to-treat obsessive-compulsive disorder with comorbid depression under treatment with esketamine and concomitant psychotherapy - Kaltenboeck, Alexander; Foerster, Elisa; Strafner, Sabrina; Demal, Ulrike; Mossaheb, Nilufar; Friedrich, Fabian (Frontiers in Psychiatry, 2023)
A 28-year-old man was admitted to our psychiatric ward with severe obsessive-compulsive disorder (OCD) and comorbid depression. At intake, obsessive-compulsive symptoms were present most time of the day and were related to an intense fear of causing interpersonal misunderstandings. Various treatment attempts, including cognitive-behavioural therapy (CBT) with exposure and response prevention (ERP), selective serotonin reuptake inhibitors, clomipramine, and add-on antipsychotics were either ineffective and/or were not tolerated, and the patient’s condition worsened progressively. Following an in-depth multidisciplinary team discussion and a shared decision-making process, an off-label treatment trial with esketamine and concomitant psychotherapy was started. The patient received 10 esketamine + psychotherapy sessions over a period of about 2 months, followed by two maintenance sessions in about 3-week intervals. After this, he was discharged into regular outpatient care where he continued to receive maintenance esketamine treatment every 4–6 weeks and, independent of this, individual CBT. Following the establishment of esketamine with concurrent psychotherapy, the patient exhibited a remarkable clinical improvement. Obsessive-compulsive symptoms showed a clear and sustained response (Y-BOCS before treatment >35, Y-BOCS at week 8 = 23, Y-BOCS at week 26 = 14). Paralleling this, depressive symptoms also decreased (MADRS before treatment = 47, MADRS at week 9 = 12, MADRS at week 26 = 3). At a naturalistic follow-up at week 66, obsessive-compulsive symptoms were still mild (Y-BOCS = 13), and depression was still in remission (MADRS < 6). This clinical case suggests that (es)ketamine plus concomitant psychotherapy may hold promise as a therapeutic strategy for difficult-to-treat OCD and depression and its full clinical potential should be evaluated in more comprehensive future studies.